`y = (t^2 + 2)/(t^4 - 3t + 1)` Differentiate.

Textbook Question

Chapter 3, 3.2 - Problem 15 - Calculus: Early Transcendentals (7th Edition, James Stewart).
See all solutions for this textbook.

1 Answer | Add Yours

balajia's profile pic

balajia | College Teacher | (Level 1) eNoter

Posted on

`y(t)=(t^2+2)/(t^4-3t+1)`

`y'(t)=(2t(t^4-3t+1)-(4t^3-3)(t^2+2))/(t^4-3t+1)^2`

`y'(t)=(-2t^5-8t^3-3t^2+2t+6)/(t^4-3t+1)^2`

``

We’ve answered 318,911 questions. We can answer yours, too.

Ask a question